2010
DOI: 10.1016/j.visres.2010.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Ocular wavefront aberrations in the common marmoset Callithrix jacchus: Effects of age and refractive error

Abstract: The common marmoset, Callithrix jacchus, is a primate model for emmetropization studies. The refractive development of the marmoset eye depends on visual experience, so knowledge of the optical quality of the eye is valuable. We report on the wavefront aberrations of the marmoset eye, measured with a clinical Hartmann-Shack aberrometer (COAS, AMO Wavefront Sciences). Aberrations were measured on both eyes of 23 marmosets whose ages ranged from 18 to 452 days. Twenty-one of the subjects were members of studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…During normal visual development, chick, marmoset and rhesus monkey eyes display a decrease in HOAs over time, similar to the reduction in neonatal refractive error. A myopigenic stimulus such as imposed hyperopic defocus or form deprivation results in significantly greater ocular HOAs associated with the development of significant ametropia compared to untreated eyes (Figure A); however, both the treated and untreated eyes show a reduction in HOAs over time (Figure B). The increase in ocular HOAs observed in chicks reared with monocularly imposed negative lenses and diffusers are predominantly due to changes in third order RMS (root mean square wavefront error), while fourth order and spherical aberration RMS were minimally affected.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…During normal visual development, chick, marmoset and rhesus monkey eyes display a decrease in HOAs over time, similar to the reduction in neonatal refractive error. A myopigenic stimulus such as imposed hyperopic defocus or form deprivation results in significantly greater ocular HOAs associated with the development of significant ametropia compared to untreated eyes (Figure A); however, both the treated and untreated eyes show a reduction in HOAs over time (Figure B). The increase in ocular HOAs observed in chicks reared with monocularly imposed negative lenses and diffusers are predominantly due to changes in third order RMS (root mean square wavefront error), while fourth order and spherical aberration RMS were minimally affected.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“…Similarly, the magnitude of coma and trefoil RMS (both third order terms) increased in monkeys who developed refractive errors from imposed defocus and form deprivation . Coletta et al also showed strong interocular correlations for each radial order of HOAs, except third order RMS, in monocularly form‐deprived marmosets.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a mammal, shows a rapid ocular development, responds to lens-induced blur, is easy to raise and handle, and optical measurements are feasible. We have previously reported optical aberration measurements (using Hartmann Shack wavefront sensors) in other animal models, such as chickens [5,6], marmosets [7], macaques [8] and mice [9]. However, despite the increasing use of the guinea pig model, and extensive research on the regulation of its eye growth (in terms of axial length and refractive error) [4,10,11], there is scarce information on its optical properties in vivo.…”
Section: Introductionmentioning
confidence: 99%